Pongo / Errissa Kyss - Kyss, Errissa (Faculty of Art and Design, 2021)
Pongo is a 2D animation about the hopes and struggles of the Orangutans. The name Pongo is based on the scientific name of the Orangutans. Pongo movie is mainly inspired by the real situation happening in Malaysia regarding the endangered species of Orangutans which are being put into a desperate condition because of the human activities. The main characters in Pongo are Patimah, Piman, Piyah and Pian. Patimah is a mother of the triplets, Piman, Piyah and Pian. Each of the characters have different identity and personality. In Malaysia, Orangutans is one of the critically endangered species, mainly because of human activities. It is estimated that the Orangutans will extinct within 10 years unless proactive action is taken to preserve the forest. Due to this issue, Pongo is created to portray the hopes and struggles of the Orangutans in today’s world. Pongo hopes to be a platform to reach the audience and create awareness about the life of Orangutans. It is believed that Pongo would be able to compete with the international industry based on the strength and the important message of the movie. The objective and aim of Pongo are to educate and be a platform to create awareness about the extinction of Orangutans. At the same time, Pongo hopes to be able to entertain and communicate the message using the dramatic characters. Pongo, Escape to Future Hope !